Accelerating adaptation to extreme weather in Europe - Matthew E. Kahn (EconPol Forum, 2025)
Europe lags behind the United States in investing in weather resilience. Durable real estate capital is at greater risk. Migration facilitates adaptation. Government policies often have unintended consequences for resilience. Need for metrics to benchmark adaptation progress both within and across European nations and over time.
Keywords: 330